2017
DOI: 10.1039/c7mh00677b
|View full text |Cite
|
Sign up to set email alerts
|

High throughput fabrication of cell spheroids by templating water-in-water Pickering emulsions

Abstract: We report a simple technique for the high throughput generation of tissue spheroids based on the encapsulation of dispersed adherent cells in particle-stabilized water-in-water emulsions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“… 19 21 Cell encapsulation by Pickering emulsions has become useful for various applications, such as encapsulation of microbial cells to protect from pH changes, 22 developing biopesticide formulations based on Bacillus thuringiensis (Bt), 23 platform for enzymatic reaction, 24 , 25 cellular capsules based on liquid marbles, 26 and encapsulation of adherent cells in water-in-water emulsions for tissue engineering. 27 …”
Section: Introductionmentioning
confidence: 99%
“… 19 21 Cell encapsulation by Pickering emulsions has become useful for various applications, such as encapsulation of microbial cells to protect from pH changes, 22 developing biopesticide formulations based on Bacillus thuringiensis (Bt), 23 platform for enzymatic reaction, 24 , 25 cellular capsules based on liquid marbles, 26 and encapsulation of adherent cells in water-in-water emulsions for tissue engineering. 27 …”
Section: Introductionmentioning
confidence: 99%
“…This technique initially confines the cells within emulsion droplets and then increases the concentration of the constant phase to impose osmotic pressure to fabricate spheroids within a very short time. 62,63 This results in the encapsulation of the cells in the DEX emulsion drops due to the higher affinity of the cells to the DEX phase, as mentioned above. Cell-cell interactions are strongly promoted with the emulsion droplets, which assists the formation of 3D cell clusters, termed clusteroids.…”
Section: Microdroplet Methodmentioning
confidence: 95%
“…Since fluorescein dissociates in water, its crossing of the cell membranes is hindered by its ionic charge, which results in the accumulation of the fluorescent byproduct inside the intact cells. 23,24 This indicates that the cell membranes are intact and the cells are viable.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…Recently, Das et al reported a rapid, expandable technique for the production of tissue globules from human embryonic kidney cells (HEK293) by trapping them in w/w Pickering emulsion droplets. 23,24 Their technique is based on the formation of w/w Pickering emulsions, in which cells are efficiently distributed in emulsion droplets. In their method, the interfacial tension of the aqueous DEX phase in the droplets, where the cells partition preferentially, is used to wrap the cells in separate compartments, and then the droplets are shrank by changing the osmotic balance of the two aqueous phases (ATP), thus rapidly driving the cells from larger and loosely packed drops to mostly spherical cell clusters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation